A Case Report of Anorexia Nervosa with Slimmer’s Palsy in a 14-Year-Old Girl - Kusen, Ivona; McDevitt, Sara; Venketram, Jayenthrie; Rampal, Rakesh; Barisic, Jelena Vojnic (Archives of Clinical and Medical Case Reports, 2025)
We are outlining the case of 14 years old girl presented to regional eating disorder services for the assessment and management, following the GP (general practitioner) referral. She presented with significant and rapid weight loss of 23 kg over five months’ time, due to food intake restriction, accompanied by a persistent pattern of behaviours to prevent weight restoration including excessive exercise regime, carbohydrates restriction and fluids overload. The vicious cycle of eating disorder and accompanied behaviours that resulted with significant weight loss led to development of physical complications of the eating disorder. She developed right sided peroneal neuropathy (Slimmer’s palsy), which is a rare complication especially in child and adolescent population, that caused ankle movements restriction, inability to walk properly and compensatory high stepping gait. Along with peroneal neuropathy, she displayed number of physical and mental health symptoms related to the eating disorder. Although peroneal palsy has multifactorial aetiology, this case clearly demonstrates reversible cause due to mechanical damage of peroneal nerve in a context of weight loss, and shows how early recognition and management are crucial steps towards recovery and prevention of long-term impairment or disability.